Effectiveness and feasibility of online fertility preservation decision aids for young female patients with cancer: a systematic review protocol - Andy SK Cheng; Yinglong Duan; Jianfei Xie; Ning Qin; Ziyu Wan; Yue Kang; Yating Luo (BMJ Open, 2023)
Introduction Cancer diagnosis and treatment can impair fertility, and younger female patients with cancer have a particularly strong need for fertility preservation. Fertility preservation decision aids are thought to help patients make proactive and informed treatment decisions. This systematic review aims to assess the effectiveness and feasibility of online fertility preservation decision aids for young female patients with cancer.Methods and analysis PubMed, Web of Science Core Collection, Embase, The Cochrane Central Register of Controlled Trials, PsycINFO and CHINAL, along with three grey literature sources (Google Scholar, ClinicalTrials.gov and WHO International Clinical Trials Registry Platform), will be searched from each database’s establishment to 30 November 2022. Two trained reviewers will independently screen the articles, and the data extraction and methodological quality of eligible randomised controlled trials and quasiexperimental studies will be assessed. A meta-analysis will be performed using Review Manager V.5.4 (Cochrane Collaboration) software, and heterogeneity will be assessed using I² statistics. If a meta-analysis is not possible, a narrative synthesis will be done.Ethics and dissemination Since this systematic review is based on published data, no ethical approval is required. The study’s findings will be disseminated through peer-reviewed publications and conference presentations.PROSPERO registration number CRD42022363287.